Treatment of Herpes Simplex Virus Infections in Pediatric Patients: Current Status and Future Needs - James, SH (2010)
Herpes simplex virus type 1 (HSV-1) and type 2 (HSV-2) are members of the Herpesviridae family and are characterized by their ability to establish latency after primary infection and subsequently reactivate. HSV infections in the neonatal and pediatric populations range from uncomplicated mucocutaneous diseases to severe, life-threatening infections involving the central nervous system (CNS). The antiviral agent acyclovir has significantly improved treatment outcomes of HSV infections, including the frequency of mucocutaneous recurrences and mortality associated with CNS and disseminated infections.